Fashionable Hybrids: Iris van Herpen and the Metamorphoses of Coded Couture - Calefato, Patrizia (E|C, 2023)
This article starts from the idea that the fashionable clothed body is a fetishis t hybrid (Latour 1992, 1994, 2005; Entwistle 2016; Volontè 2017). This conception connects both Latour s idea of hybrids as a way of reassemblying culture with nature and Walter Benjamin s (1999) conception of fashion as the sex appeal of the inorganic. According to Benjamin, the relationship between organic and inorganic is produced, in a philosophically disconcerting way, as an inversion of meaning between the living body and the corpse, in other words, as fetishism. On the contrary, Latour s hybri ds are social subjects with agency in themselves. In the light of this theoretical framework, the chapter analyses the work of the Dutch designer Iris van Herpen, especially in her collections of 2021 and 2022 which are based on the active role of objects: clothes, fabrics, technologies, atmospheric agents such as the wind etc. In this way, the designer produces different forms of hybridization among the human body, the animal and plant worlds, and the digital ecosystem. The article will highlight the forms of the reciprocal agency between human bodies and the bodies of objects, between emotions and new technological materials, between sustainable ICTs and aesthetics in van Herpen s work showing how the current idea of coded couture is released from its m ere algorithmic functionality.